Planning analysis, planning approaches and design of the new city of Tis In line with the regional development of Makran Coast - Badil Sancholi; Maryam Karimian Bostani; Masoumeh Hafez Rezazadeh (تحقیقات کاربردی علوم جغرافیایی)
The establishment of new cities and settlements and the development of economic and industrial activities on the shores of Makran, is inevitable, and since the creation and development of new cities has been one of the policies in land management in recent decades, planning and designing a new city in Regional development orientation of this region is essential. Therefore, in this regard, the purpose of the present study is the analysis of planning approaches and design of the new city of Tis in order to develop the region of Makran beaches. The present study is applied in terms of nature and descriptive-analytical in terms of method. Theoretical studies were collected using documentary method, and research data and information were collected using interviews and questionnaires. The statistical population of the study includes specialists, administrators, university professors and experts. Using purposive sampling method, 183 experts were determined as the sample size. To analyze the variables and approaches of the research, first using the method of interviews and interactive discussions with experts and specialists as a statistical sample of the research, each of the planning approaches of new cities was examined. Also, descriptive tests, Spearman correlation test and hierarchical analysis model were used to analyze the data. The results showed that the exit of the region from deprivation and vulnerability, creating a scientific and educational hub in the region, and designing a new and smart city to create a sustainable city have been the most important approaches explaining the planning and design of the new city. Also, there is a significant and positive relationship between planning approaches and design of the new city of Tis and the development of Makran beaches, and among these, the investment variable in Makran beaches has the highest relationship with regional development in the study area